Empowerment of Wanagiri Coffee Farmer Groups Through the Development of Marketing and Business Management Strategies with the Concept of Zero Waste to Support the Green Economy - Luh Suriati; Kaca Nyoman; Wirajaya Anak Agung Ngurah Mayun; Rabani I Gusti Agung Yogi; Putri Kadek Sintya Pradnyani; Purwanti Ni Putu Ayu Sintya (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Coffee is one of the agricultural commodities that has high economic value. Arabica Coffee (Coffea arabica L.) Wanagiri is one of the leading coffee varieties in Indonesia that is now becoming popular because it contains several bioactive components, such as phenolic compounds and flavonoids, antioxidant activity, and very specific aromas and tastes. Coffee production, in addition to producing coffee beans, also produces 55-60% of coffee waste in the form of cherry pulp, cherry husks, parchment, silver husks, and used coffee powder. The assistance of coffee farmer groups in Wanagiri Village, Sukasada District, Buleleng Regency, is very necessary to produce superior Arabica coffee. The program implementation method includes four stages, namely observation and analysis of needs, program preparation (preparation), implementation (training, mentoring, or counseling), and evaluation and monitoring. This activity concluded that farmer groups now have a better understanding of neat business management and can formulate more modern marketing strategies (digitalization) to increase the selling value of Wanagiri coffee. Farmer groups are able to manage coffee waste (cherry peels/pulp) into products of economic value, such as compost or other derivative products, thereby reducing environmental impact while creating alternative sources of income. The integration between efficient business management and zero-waste management has successfully supported the creation of sustainable agricultural practices in Wanagiri Village, which is in line with green economy principles. Contribution to Sustainable Development Goals (SDGs):SDG 1: No Poverty; SDG 2: Zero Hunger; SDG 12: Responsible Consumption and Production; SDG 13: Climate Action; and SDG 15: Life on Land